Pengaruh Aromaterapi Lavender (Lavandula angustifolia) pada Mahasiswa Kedokteran yang Mengalami Insomnia: Hasil Penelitian - Bakhriansyah, Mohammad; Rizky, Nabilla; Limantara, Sherly (Cermin Dunia Kedokteran, 2025)
Introduction: The first line of therapy for insomnia disorders is a psychological approach and anti-insomnia drugs. One of the recommended alternative therapies is lavender aromatherapy (Lavandula angustifolia). This study aimed to determine the effect of lavender aromatherapy on insomnia among medical students of the Faculty of Medicine and Health Sciences, Universitas Lambung Mangkurat, Banjarmasin, Indonesia. Methods: The design was a clinical trial with a one-group pretest-posttest design involving 48 students in October 2023. Subjects were selected by consecutive sampling techniques, and data were collected online by Google Form. The Jakarta biological psychiatry study group questionnaire–insomnia rating scale (KSPBJ-IRS) was used to assess the level of insomnia before and after aromatherapy. Data were analyzed using the Wilcoxon signed-rank statistical test with a 95% confidence level. Results: This study showed that before aromatherapy, 50% of subjects experienced mild and severe insomnia. After aromatherapy, 39.6% of subjects did not experience insomnia, while 56.2% and 4.2% experienced mild insomnia and severe insomnia, respectively. This relationship was statistically significant (p = 0.0005). Conclusion: These results indicate that lavender aromatherapy can significantly improve insomnia.